Genetic relationships among Vietnamese local pigs investigated using genome‐wide SNP markers. (15th January 2018) - Ishihara, S.; Arakawa, A.; Taniguchi, M.; Luu, Q. M.; Pham, D. L.; Nguyen, B. V.; Mikawa, S.; Kikuchi, K.
Summary: Vietnam is one of the most important countries for pig domestication, and a total of 26 local breeds have been reported. In the present study, genetic relationships among the various pig breeds were investigated using 90 samples collected from local pigs (15 breeds) in 15 distantly separated, distinct areas of the country and six samples from Landrace pigs in Hanoi as an out‐group of a common Western breed. All samples were genotyped using the Illumina Porcine SNP60 v2 Genotyping BeadChip. We used 15 160–15 217 SNPs that showed a high degree of polymorphism in the Vietnamese breeds for identifying genetic relationships among the Vietnamese breeds. Principal components analysis showed that most pigs indigenous to Vietnam formed clusters correlated with their original geographic locations. Some Vietnamese breeds formed a cluster that was genetically related to the Western breed Landrace, suggesting the possibility of crossbreeding. These findings will be useful for the conservation and management of Vietnamese local pig breeds.